Encountering Russianness in philosophy: the historiosophical conservatism of N.Danilevsky and K.Leontiev. Interpretations, assessments and approachyes in the western historiography - Martynyuk, I.S. (Культура народов Причерноморья, 1999)
Being an educated and noble Frenchman, Marquis de Custine could easily justify his judgements and vision of what Europeanness really was and how it looked like. In the nineteenth century European mirror of Otherness, Russia's geographical image merged with the domain of Eastern backward lands excluded by philosophic geography from Europe proper and shifted to Asia. Produced within the strategic discourse, focussed on the Eastern question, and accompanied by the fundamental division of Europe between the culturally superior West and the inferior East, the theme of the "Asiatic barbarian at the gates of Europe" dominated the European constructions of Russia for almost two centuries. Given the self-sufficient character of such an attitude, there was no necessity of identifying of what Russianness precisely meant in terms of self-perception and mentality.